1997
DOI: 10.1590/s1516-31801997000600005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body composition on the bone mass of postmenopausal women

Abstract: Aims:To investigate the influence of body weight (BW), fat mass (FM) and lean mass (LM) on the bone mineral density (BMD) of several areas of the skeleton. Participants: Sixty one white postmenopausal women (50.1:t4.8 years). Measurements: Measurement of BMD by dual energy x-ray absorptiometry. The results were analyzed by linear regression and the slopes of each curve were compared. Results: The results showed that the correlations between BW, FM and LM to BMD were positive, whilst the correlations between ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Specifically focusing on our findings, it may be that the lower weight (8.1 kg lower) and BMI (3.3 kg/m 2 lower) relative to the controls, which is characteristic of individuals with osteoporosis, 25 , 26 may have had an influence. Weight may have negatively influenced the ability to displace the COP.…”
Section: Discussionmentioning
confidence: 77%
“…Specifically focusing on our findings, it may be that the lower weight (8.1 kg lower) and BMI (3.3 kg/m 2 lower) relative to the controls, which is characteristic of individuals with osteoporosis, 25 , 26 may have had an influence. Weight may have negatively influenced the ability to displace the COP.…”
Section: Discussionmentioning
confidence: 77%
“…Aloia et al [22] showed that body fat was not related to total or regional bone mineral measurements in white women (aged 51.1 B 10.8 years), but they found that muscle mass, which was increased with obesity, was related to bone mineral concentrations. Malone et al [23] showed that BMD was positively correlated with body weight, fat mass, lean mass and negatively correlated with age in postmenopausal women (50.1 B 4.8 years). They demonstrated that lean tissue mass was the main factor that influenced BMD in almost all areas (total body, femoral neck).…”
Section: Discussionmentioning
confidence: 99%
“…Their authors [19,20] stressed the importance of total fat mass in bone mineral protection. To date, the association between bone mass and lean tissue mass has only been shown in younger women [21][22][23]. Aloia et al [22] showed that body fat was not related to total or regional bone mineral measurements in white women (aged 51.1 B 10.8 years), but they found that muscle mass, which was increased with obesity, was related to bone mineral concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Increased fat mass is associated with a decrease in muscles and bone masses (10). Therefore, body composition appears to be another factor affecting the reduction of bone density (11).…”
mentioning
confidence: 99%